(untitled) (Journal of Asian Development Studies, 2023)
Regarding the spread of plants and how people might use urban biodiversity, nursery management is essential for supplying resources for healthy plants. The current survey was conducted at Madina Nurseries in Pattoki, Punjab province, Pakistan. The current state of affairs, varied management techniques used by gardeners to run their nurseries, and the spread of different types of decorative plants served as the foundation for this survey. The main goals of this study were to enhance the present condition of nurseries and offer recommendations on the issues highlighted. Several characteristics include plant identification, nursery size, soil type, irrigation system, weeding, fertilizer usage, and propagation technique, respectively. The right fertilizer has to be utilized at the right time for plant growth and nurseries to flourish. It was acknowledged that the unidentified diseases and production of high-quality plants are associated with germplasm unit facilities.